Facile Synthesis of Catalyst Free Carbon Nanoparticles From the Soot of Natural Oils - Nadeem, Sohail; Javed, Mohsin; Iqbal, Shahid; Mohyuddin, Ayesha; Mahmood, Qaiser; Abbas, Qasir; Alfryyan, Nada; Alqahtani, Mashael D.; Alotaibi, Mohammed T.; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; et al. (Frontiers in Materials, 2022)
The growth of carbon nanostructures from vegetable oils using a modified conventional approach is a simple and environmentally friendly technology with controllable features. The goal of this study is to develop a simple and environmentally friendly process for making carbon nanoparticles using commercially available, low-cost vegetable oils. The technique involves the controlled burning of “Mustard”, “Olive”, and “Linseed” oils using the traditional clay lamps and collecting the carbon soot on a ceramic plate. The prepared carbon nanoparticles were purified through sonication and subjected to characterization using powder X-ray diffraction, SEM, Fourier transformed infrared, Thermogravimetric and differential scanning calorimetric analyses. The average particle size of carbon nanoparticles as investigated by powder X-Ray Diffraction analyses was found to be 18 nm, 24nm and 57nm for mustard, olive and linseed oils respectively. SEM analyses revealed the surface morphology of these carbon nanostructures as spherical particles. Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) providing knowledge about the thermal stability of these carbon nanoparticles. The synthesized carbon nanoparticles were screened for antibacterial activities against different species (e.g. Pseudomonas aeruginosa, Streptococcus haemolyticus, Proteus refrigere and Staphylococcus aureus) and fruitful results have been obtained.